Current tobacco use among adults: a community-based study in urban area of Thanlyin township, Yangon region, Myanmar - Oo, Win M.; Aung, May S.; Lwin, Kay T.; Bo, Thae’ Z. C.; Mya, Kyaw S. (International Journal Of Community Medicine And Public Health, 2017)
Background: The identification, prevention and control of the common risk factors are the basic element in prevention and control of NCDs. However, the paucity of information on risk factors is one of the major challenges in the prevention and control of these diseases. The use of tobacco is one of the main risk factors of major NCDs. Therefore, this study was conducted to determine the prevalence, and socioeconomic and demographic determinants of current tobacco use among adults residing in urban area of Thanlyin Township, Yangon Region. Methods:A cross-sectional study was conducted among 468 adults. Multi-stage random sampling was applied. Data entry and analysis was done using Stata 11.0 statistical package. Results: The prevalence of current smoking, current use of smokeless tobacco and current tobacco use were 27.6%, 35.7% and 48.1%, respectively. Age, sex, marital status and occupation were significantly associated with both current smoking and current use of smokeless tobacco. There was a significant decreasing trend of current smokeless tobacco use across the levels of education. Besides, age, sex, education and occupation were detected as significant determinants of current tobacco use. Conclusions:There is an urgent need to curb the use of tobacco in urban area, especially among males and young adults. Tobacco control policy in Myanmar should be strengthened or reinforced to reduce tobacco consumption in the country. Education status of the population should also be improved.